Automatic AC Current Controller as Input Adapter Power Supply Laptop Based on ESP32 - Kiayi, Muchlis Alfajrin; Musa, Wahab; Nasibu, Iskandar Zulkarnain (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Frequently, laptop users forget to disconnect or connect the power supply adapter when the battery needs to be charged or fully charged due to they are too focused on using the laptop. This condition can cause problem with laptop batteries and one of which is overcharging. Thus, keeping the laptop battery healthy is advantageous and one of them is to make it last longer. In addition, when the battery is faulty, the replacement of it also requires a lot of money. To deal with this condition, it is necessary to have a design tool that can automatically cut off the AC voltage on the laptop power supply adapter which will be equipped with software. This current research employed development research method and aimed to create a tool comprising hardware and software that could cut off the AC voltage to the laptop power supply adapter automatically based on the laptop battery percentage status.